Foreign direct investment, technology accumulation and domestic investment in Malaysia - Andaman, Gul (2018)
The Malaysian economy progressed dynamically over time due to the vibrant industrial policy which focused on expanding the manufacturing sector and increasing the inward foreign direct investment (IFDI). This contributed towards technology accumulation in the domestic manufacturing sector and enabled firms to become part of global supply chain leading to higher outward foreign direct investment (OFDI) and ameliorating domestic investment. However, after Asian financial crisis in 1997, the economic growth rate decelerated due to the sluggish pace of technology accumulation from IFDI. Horizontal and vertical linkages with the foreign firms in the Malaysian manufacturing sector weakened and the manufacturing sector specific IFDI growth rate itself witnessed a significant fall in the region. Since technology accumulation leads to higher OFDI, limited increase in that factor may have been responsible for lower OFDI that slithered away inauspiciously since 2005 particularly from the manufacturing sector and overall from all sectors since 2014 further exacerbating the state of affairs. Other issues such as counterproductive macroeconomic situation reflected in slow economic growth rate, high inflation and falling trade surplus, and decreasing institutional quality due to higher crime rates and corruption, also could have played their part in restricting OFDI from Malaysia. Higher OFDI can have a positive impact on domestic investment but due to stagnant local investment as percentage of GDP since Asian financial crisis in 1997, it .appears that it did not complement OFDI. Encumbered with such possibilities and issues, Malaysian policymakers shall find it more challenging to gain higher technology transfer from IFDI, raise cross border investments and crowd-in domestic investment from higher OFDI which can also be a hurdle in the aim of achieving a high income nation status by the year 2020. Therefore, this study analyzes the following objectives which can help in addressing the issues and in devising more effective policies. Firstly, it estimates the impact of IFDI related horizontal, backward and forward linkages on technology accumulation of the domestic manufacturing sector. It is a panel data analysis and based on the diagnostics, fixed effects estimator has been employed. Secondly, it investigates the factors that can generate higher OFDI and thirdly, it analyzes the impact of OFDI on domestic investment. For fulfilling second and third objectives, Autoregressive Distributed Lag (ARDL) methodology has been utilized. The analyses reveal that the technology accumulation of the domestic manufacturing sector falls due to weak horizontal and backward linkages whereas forward linkages significantly increase it. Technology accumulation, trade surplus, appreciation of Ringgit Malaysia (RM) and GDP contribute to high OFDI. Institutional factors such as high law and order, low corruption and low economic risk rating also significantly increase OFDI. Empirical outcome also shows that OFDI crowds-out domestic investment in Malaysia. Such outcomes imply that the policymakers should primarily increase technology accumulation by focusing on high-end tasks across all sectors, accelerating research and development (R&D) and developing domestic suppliers, especially in the import-competing sector. Government support and domestic spin-offs by international Malaysian-based firms are also essential in this regard. Besides, more IFDI should be channeled towards downstream sector as that would provide more growth opportunities to local suppliers. Such policies can improve horizontal and backward linkages. To raise OFDI, the policies should yet again focus on technology accumulation, increase high value added exports and reduce hi-tech import burden pacing up trade surplus. Counteracting corruption and crime rate can also accelerate OFDI. Increasing technology-seeking OFDI and domestic presence in the upstream sector, especially in subsectors where foreign presence is higher such as pharmaceuticals, medical devices and electrical and electronics (E&E), shall not only increase OFDI but also crowd-in domestic investment providing opportunities for local suppliers to become part of the supply chain.